2016
DOI: 10.1186/s12909-016-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Spanish version of the Jefferson Scale of Empathy: making sense of the total score through a second order confirmatory factor analysis

Abstract: BackgroundEmpathy is a key aspect of the physician-patient interactions. The Jefferson Scale of Empathy (JSE) is one of the most used empathy measures of medical students. The development of cross-cultural empathy studies depends on valid and reliable translations of the JSE. This study sought to: (1) adapt and assess the psychometric properties in Spanish students of the Spanish JSE validated in Mexican students; (2) test a second order latent factor model.MethodsThe Spanish JSE was adapted from the Spanish J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 43 publications
8
28
2
Order By: Relevance
“…The mean empathy score of the sample in the present study is similar to that found in Japan [5], China [7], Korea [9], India [10], and Iran [11] and relatively lower than the mean scores reported in some Western countries, such as Spain [12], America [13], and Germany [14]. Thus, Asian students tend to have similar levels of empathy but lower than do Western students (Additional file 1: Table S1 in Supplemental Data).…”
Section: Discussionsupporting
confidence: 79%
“…The mean empathy score of the sample in the present study is similar to that found in Japan [5], China [7], Korea [9], India [10], and Iran [11] and relatively lower than the mean scores reported in some Western countries, such as Spain [12], America [13], and Germany [14]. Thus, Asian students tend to have similar levels of empathy but lower than do Western students (Additional file 1: Table S1 in Supplemental Data).…”
Section: Discussionsupporting
confidence: 79%
“…of standing in patients' shoes and perspective caring indicates the need for improving theoretical attitudes of the physics towards the clinical significance of empathy and to strength their relevant psychological skills. Both of these needs would be at least partially met by training 2,10. The average level of empathy observed in our physicians (100.7) compares with that in some previous studies which have used a similar scale.…”
supporting
confidence: 80%
“…Although the effect appears only in 5% of asymptomatic patients, its prevalence in patients with PCOS and oligomenorrhea is about 20% [2]. Body mass index (BMI) and nulliparity are two main risk factors for EH.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the 3-factor structure was also confirmed in medical students from two Spanish medical schools (Ferreira-Valente et al 2016), and in Turkish medical students (Bilgel and Ozcakir 2017). …”
Section: Resultsmentioning
confidence: 63%